Reduced immunogenicity of a live Salmonella enterica serovar Typhimurium vaccine in aged mice - Allen, Jessica C.; Toapanta, Franklin R.; Baliban, Scott M.; Sztein, Marcelo B.; Tennant, Sharon M. (Frontiers in Immunology, 2023)
Non-typhoidal Salmonella (NTS) is responsible for a high burden of foodborne infections and deaths worldwide. In the United States, NTS infections are the leading cause of hospitalizations and deaths due to foodborne illnesses, and older adults (≥65 years) are disproportionately affected by Salmonella infections. Due to this public health concern, we have developed a live attenuated vaccine, CVD 1926 (I77 ΔguaBA ΔclpP ΔpipA ΔhtrA), against Salmonella enterica serovar Typhimurium, a common serovar of NTS. Little is known about the effect of age on oral vaccine responses, and due to the decline in immune function with age, it is critical to evaluate vaccine candidates in older age groups during early product development. In this study, adult (six-to-eight-week-old) and aged (18-month-old) streptomycin pre-treated C57BL/6 mice received two doses of CVD 1926 (10^9 CFU/dose) or PBS perorally, and animals were challenged orally with 10^8 CFU of wild-type S. Typhimurium SL1344 at 4 weeks postimmunization. Compared to PBS-immunized mice, adult mice immunized with CVD 1926 had significantly lower S. Typhimurium counts in the spleen, liver, and small intestine upon challenge. In contrast, there were no differences in bacterial loads in the tissues of vaccinated versus PBS aged mice. Aged mice exhibited reduced Salmonella-specific antibody titers in the serum and feces following immunization with CVD 1926 compared to adult mice. In terms of T cell responses (T-CMI), immunized adult mice showed an increase in the frequency of IFN-γ- and IL-2-producing splenic CD4 T cells, IFN-γ- and TNF-α-producing Peyer’s Patch (PP)-derived CD4 T cells, and IFN-γ- and TNF-α-producing splenic CD8 T cells compared to adult mice administered PBS. In contrast, in aged mice, T-CMI responses were similar in vaccinated versus PBS mice. CVD 1926 elicited significantly more PP-derived multifunctional T cells in adult compared to aged mice. These data suggest that our candidate live attenuated S. Typhimurium vaccine, CVD 1926, may not be sufficiently protective or immunogenic in older humans and that mucosal responses to live-attenuated vaccines decrease with increasing age.